Classification in the Wider Philosophical Perspective of Informational Ontology. Lecture 1: Bibliographic Classifications - Gnoli, Claudio (Journal of Information and Knowledge, 2025)
Authors in library and information science like Dewey, Otlet, Bliss, Ranganathan, Vickery, Kyle, Foskett, Austin and Dahlberg have developed a rich corpus of classification theory and practice, covering important techniques like hierarchical subdivision, facet analysis and ordering of arrays by integrative levels. The advent of digital information offers an opportunity to organize information using such techniques; but this heritage has often been forgotten in the illusion that automation has made it unnecessary. Nowadays bibliographic classification is subsumed in the field of knowledge organization, which covers the conceptual ordering of contents in libraries, archives, museums, digital collections and knowledge in general. We propose a broad view of knowledge organization as an intellectual guide to learning and scholarship grounded in philosophical ontology. Established classification principles can contribute their techniques for the production of general schemes of phenomena.